1991
DOI: 10.1152/jn.1991.65.6.1392
|View full text |Cite
|
Sign up to set email alerts
|

Regional cerebral blood flow during voluntary arm and hand movements in human subjects

Abstract: 1. Regional cerebral blood flow (rCBF) was measured using positron emission tomography in six normal volunteers while at rest and while performing four different repetitive movements of the right arm. 2. The four movements were performed in random order and consisted of abduction of the index finger, making a fist, sequential thumb to digit opposition, and shoulder flexion. All the movements were done at the same rate, using an auditory cue and involved displacements through similar amounts of the physiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
194
5
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 555 publications
(232 citation statements)
references
References 0 publications
32
194
5
1
Order By: Relevance
“…Moreover, in the present study we also attempted to quantify network activity by means of absolute CBF. The absolute CBF values extracted for both networks and during rest or task condition, as well as the percentage increase were in agreement with values reported in literature ( (Wang et al 2003b) ASL/ (Colebatch et al 1991) PET). The ANOVA results of the CBF values further demonstrated the stability and thus test-retest reliability of the presented approach.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, in the present study we also attempted to quantify network activity by means of absolute CBF. The absolute CBF values extracted for both networks and during rest or task condition, as well as the percentage increase were in agreement with values reported in literature ( (Wang et al 2003b) ASL/ (Colebatch et al 1991) PET). The ANOVA results of the CBF values further demonstrated the stability and thus test-retest reliability of the presented approach.…”
Section: Discussionsupporting
confidence: 90%
“…However, occasional muscular activity was observed in all but one of the patients during the scanning period. Separating movement related activations from pain related activations is a potential problem in all functional imaging studies of pain since any observed movement or unobserved muscle tension may activate the postcentral gyrus in concert with the motor cortex (Colebatch et al, 1991;Hsieh et al, 1995b). In addition, movement intention/preparation may increase the activity in the motor cortex (Hsieh et al, 1994;Deiber et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…(3) Lesion studies in monkeys and observations in humans with brain lesions indicate that MI is critical in the performance of discrete movements of fingers and other parts of the body (review in [24]). PET studies have shown that MI is activated as much by whole hand movements as by the independent movement of the fingers [5]. Simultaneous movements of two fingers causes even less activation of MI than sequential movements of these fingers with the frequency of movements being kept constant [29].…”
Section: Discussionmentioning
confidence: 99%